2003
DOI: 10.1002/ldr.580
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and losses by erosion in soils amended with sewage sludge

Abstract: In order to promote the transformation of a burnt Mediterranean forest area into a // / dehesa system, 10 t ha À1 of dry matter of the same sewage sludge in three different forms: fresh, composted and thermally-dried, were added superficially to field plots of loam and sandy soils located on a 16 per cent slope. This application is equivalent to 13Á8 t ha À1 of composted sludge, 50 t ha À1of fresh sludge and 11Á3 t ha À1 of thermally-dried sludge. The surface addition of a single application of thermally-dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 27 publications
4
40
1
5
Order By: Relevance
“…In spite of that, different organic amendments -viz. cotton gin crushed compost and poultry manure, beet vinasse, sewage sludge, organic urban solid refuse, sheep manure, cow manure, rice husk, finely chopped reeds, wheat straw, and licorice (root) dregs (Agassi et al, 1998;Albaladejo et al, 2000;Ojeda et al, 2003;Gonzalez, 2006b, 2008;Nicolás et al, 2012;Karami et al, 2012) -have commonly been used for soil conservation in agricultural and forestry soils.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of that, different organic amendments -viz. cotton gin crushed compost and poultry manure, beet vinasse, sewage sludge, organic urban solid refuse, sheep manure, cow manure, rice husk, finely chopped reeds, wheat straw, and licorice (root) dregs (Agassi et al, 1998;Albaladejo et al, 2000;Ojeda et al, 2003;Gonzalez, 2006b, 2008;Nicolás et al, 2012;Karami et al, 2012) -have commonly been used for soil conservation in agricultural and forestry soils.…”
Section: Introductionmentioning
confidence: 99%
“…The application of biosolids and proper management, can be possible ways for soil restoration. After biosolids application, plant cover is rapidly established, helping to minimize runoff and reduce water erosion (Rostagno and Sosebee, 2001;Martínez et al, 2003b;Ojeda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In central Spain, Walter et al [5] reported favorable soil and vegetation resulted from the decreased erosion and enhanced water relations that resulted from applications of 40 to 80 Mg biosolids ha −1 . Ojeda et al [6] reported similar results in north-east Spain using fresh biosolids, composted biosolids, and thermally dried biosolids.…”
Section: Introductionmentioning
confidence: 64%